Leaders in the living room - Coleman, S (2011)
This study explores the first-ever British televised prime ministerial debates with a view to understanding how they were received by the public; how they were depicted in the press and on television; and how far they registered online. Rather than asking 'who won', the aim was to understand how far the debates contributed to an improved democratic relationship between politicians and citizens. Based on a range of research methods, and involving researchers from three universities, this study contributes innovatively to the global literature on debates research.